The Transformation of Da'wah Student Activity Unit through Religious Moderation Value Education - Moh Muslih; Mohd Mizan Aslam; Diyah Nurul Fitriyati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Radicalism in the name of religion has spread and took root in various universities in Indonesia through, among others, the student activity unit (UKM). This condition needs serious attention from campus officials in order to prevent the students from radical ideology. This is because the main value of religious moderation promoted by Indonesian Ministry of Religious Affairs includes commitment to nationality, harmony, anti-violence and wisdom towards local culture, which aims to prevent radicalism from being implemented optimally, so that it can endanger student morality. This article aims to portrait the transformation process of UKM da'wah named Al-Fattah, which has been indicated to have radical ideology, into a moderate da'wah unit through religious moderation value education. This participatory action research emphasizes joint learning, participation, and organizational transformation. Through in-depth analysis, the results show that after changing the name from Lembaga Dakwah Kampus Al-Fattah to Korps Dakwah Islam Nusantara, this da'wah unit began to spread moderate Islamic values, or what commonly refer to rahmatan lil alamin. Research contributions include strengthening government programs in order to participate in realizing the religious moderation program launched by the Indonesian Ministry of Religious Affairs.